Assessment of the rate of force development scaling factor for the hip muscles. Issue 6 (16th September 2014) - Casartelli, Nicola C.; Lepers, Romuald; Maffiuletti, Nicola A.
ABSTRACT Introduction: The aim of this study was to evaluate test feasibility, validity, and reproducibility of the rate of force development scaling factor (RFD‐SF) for the hip muscles. Methods: Feasibility was assessed as the testing compliance, validity as the ability to compute the RFD‐SF from a linear regression, and reproducibility with a test–retest design in 20 healthy subjects. Reliability and agreement (reproducibility) were evaluated using intraclass correlation coefficient (ICC3, 1) and percent standard error of measurement (SEM), respectively. Results: The RFD‐SF testing protocol was completed successfully by all subjects, although the analysis had to be modified for hip rotators. Reliability was high (ICC3, 1 > 0.70) for all muscles except hip abductors (ICC3, 1 = 0.69) and internal rotators (ICC3, 1 = 0.58). Agreement was high for all muscles (SEM < 10%). Conclusions: Hip adductor, flexor, and external rotator RFD‐SF can be evaluated with confidence, provided the analysis is modified for external rotators, whereas hip abductor and internal rotator RFD‐SF assessment is not recommended. Muscle Nerve 50: 932–938, 2014